Traditional Acupuncture Meets Modern Nanotechnology: Opportunities and Perspectives. (16th July 2019) - Zhang, He; Han, Gang; Litscher, Gerhard
Abstract : Acupuncture is an ancient method in traditional Chinese medicine (TCM). Usually acupuncture needles are inserted into the body to achieve therapeutic effects. However, there are still some challenges to achieve consensuses. What is the essence or anatomy of acupuncture meridians? How does acupuncture work? How to improve acupuncture clinical therapeutic effect? These questions may be addressed by highlighting recent developments in innovative nanotechnology. The aim of this review is to elucidate the possible applications and future potential of nanotechnology in acupuncture. Nanoparticles are promising for imaging and it may gain a better understanding of the essence of meridian. Nanotechnology enables nanochips/nanosensors providing new solutions in detection reactive molecules in vivo and in real time. The connections and changing of these molecules with needle stimulation will allow insight into the mechanisms of acupuncture. Acupuncture combined with nano-TCM could provide a great potential in some type of characteristic acupuncture therapies improvement. By virtue of nanotechnology, the acupuncture needles could be innovated as multifunction toolbox. Acupuncture needles could be considered as a method for controlled drug delivery. The nanoparticulated photothermal, magnetothermal, photodynamic agents could also be filled on the surface of needle.